Evaluation of a novel line probe assay to detect resistance to pyrazinamide, a key drug used for tuberculosis treatment. (January 2018) - Driesen, M.; Kondo, Y.; de Jong, B.C.; Torrea, G.; Asnong, S.; Desmaretz, C.; Mostofa, K.S.M.; Tahseen, S.; Whitfield, M.G.; Cirillo, D.M.; Miotto, P.; Cabibbe, A.M.; et al.
Abstract: Objectives: The development of rapid molecular diagnostic assays for pyrazinamide (PZA) resistance is considered technically challenging as mutations are highly diverse, scattered along the full length of the pncA gene and not all are associated with PZA resistance. We evaluated the performance of the novel Genoscholar PZA-TB II line probe assay (PZA-LPA2; NIPRO Corporation, Japan). Methods: To evaluate the applicability of the PZA-LPA2 in clinical settings, we compared the performance of the PZA-LPA2 to a composite reference standard pncA Sanger and Illumina sequencing plus phenotypic susceptibility testing on a panel of 87 Mycobacterium tuberculosis isolates from World Health Organization (WHO) drug resistance surveys, harbouring mutations previously classified as associated or not associated with resistance according to data from peer-reviewed literature. In addition, the PZA-LPA2 was challenged against a selection of isolates with lineage-specific and non-resistance-associated mutations, for which the frequency among clinical isolates is unknown, and tested directly on 59 sputum extracts. Results: For the survey isolates, the PZA-LPA2 reached an overall agreement with the composite reference of 97.6% (80/82) or 94.3% (82/87) excluding or including heteroresistance, respectively. The PZA-LPA2 failed on 8.5% (5/59) of clinical samples; among valid results, 100% (14/14) sensitivity and 100% (7/7) specificity was reached relative to pncA Sanger sequencing. Conclusions: The PZA-LPA2 represents a valid and rapid alternative for indirect PZA susceptibility testing. Preliminary findings on clinical samples show promise for direct testing. Further studies are needed to assess the clinical risk of missing heteroresistance and falsely detecting lineage-specific, silent and nonassociated mutations.